Evaluation of the effect of nutrition-related visual education on the comfort of patients receiving hemodialysis therapy - KOSAR SAHIN, Cansu; CINAR PAKYUZ, Sezgi (Revista de Nutrição, 2022)
Objective This study aimed to evaluate the effect of visual education on the comfort of patients receiving hemodialysis therapy. Methods A randomized controlled study design was used. This study was conducted in two dialysis centers with 90 chronic hemodialysis patients. A Patient introduction form, Hemodialysis Comfort Scale-Version II, Hemodialysis Patient Fluid Control Scale, Scale for Dietary Knowledge, and Scale for Dietary Behaviors were used. In the intervention group, three interviews were conducted. In the first interview, visual education was applied, and reinforcement education ensued after 15 days. In the control group, two interviews were conducted, and no intervention was performed. Results The training program was found to have a significant effect on comfort, physical and psychospiritual ease, psychospiritual and environmental transcendence, and sociocultural ease, and a moderate effect on physical relief in the intervention group in the third month. It was determined that the visual education program applied had a large effect size on fluid control, diet knowledge, and behaviors in the intervention group. Conclusion Visual education was found to have a positive effect on the comfort status, dietary knowledge, and dietary behavior of patients receiving hemodialysis therapy.